(untitled) (Journal of Dhaka National Medical College & Hospital, 2020)
A 22 years old patient presented with complaints of weakness in all four limbs and ataxia for 2 months. He had also history of slurring of speech and inclining to right side during walking. His gait was wide based and spastic ataxic. Patient was spastic quadriparetic with subtle right sided cerebellar sign and dissociated sensory loss in both upper limb and right Hemithorax. MRI of the brain and cervical spine revealed tonsillar herniation > 12 mm in cervical canal with large syrinx from cervical cord to thoracic region. Finally, the case was diagnosed as a Chiari Type-1 Malformation. Early diagnosis and intervention by Neurosurgeon actually halted the further syrinx extension and reduce neurological deficit with improvement of daily life activities. J. Dhaka National Med. Coll. Hos. 2020; 26 (02): 33-35